The gap between potential entrepreneurship and actual entrepreneurship: an inter-continental comparative analysis - Óscar Rodil; Diana Morales (European Regional Science Association (ERSA), 2015)
The aim of this paper is to analyze the difference between the rates of potential entrepreneurship and actual entrepreneurship in European and American context, trying to identify some of the explanatory factors. For this purpose an institutional approach is used, which includes the role of various formal and informal factors related with the potential and emerging entrepreneurial activity. From an empirical point of view, the paper takes into account twenty countries from the European and American continent, covering the last decade. The results show, in general, the influence of the institutional framework on the gap between the nascent entrepreneurship and potential entrepreneurship, through formal and informal factors. We use data from the Global Entrepreneurship Monitor (GEM), which measures the entrepreneurial intention and nascent entrepreneurial activity, the World Bank and the Index of Economic Freedom (The Heritage Foundation).
Keywords: L26; E02; O52; 330; Entrepreneurship; Gap; New Institutional Economics; Europe; America